DNA MICROARRAY GENOTYPING AND VIRULENCE AND ANTIMICROBIAL RESISTANCE GENE PROFILING OF METHICILLIN-RESISTANT Staphylococcus aureus BLOODSTREAM ISOLATES FROM RENAL PATIENTS - SHORE, ANNA; COLEMAN, DAVID (My University, 2011)
Thirty-six methicillin-resistant Staphylococcus aureus (MRSA) bloodstream isolates from renal patients were genetically characterized by DNA microarray analysis and spa typing. The isolates were highly clonal, belonging mainly to ST22-MRSA-IV. The immune evasion and enterotoxin gene clusters were found in 29/36 (80%) and 33/36 (92%) of isolates, respectively.
PUBLISHED
Keywords: Immunology; Infection; Staphylococcus aureus